Optimalisasi Peran Guru Pendidikan Agama Islam dalam Membangun Sikap Keimanan dan Akhlak Mulia pada Peserta Didik - Amrizal Isa (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
This article tries to discribe about paths to optimize the teachers’ role of Islamic education in building students’ character to response moral crises happened recently among students and graduated. These paths must be conducted by goverment, educational institution and teachers as well. The goverment should make a specific political policy to strengthen Islamic education process at school or out of school in regard to curriculum changes, supporting learning sources and providing facilities and up grading teacher capacity and competency. The educational institution must attempt to make Islamic Education as a core of educational development at school by constructing sociocultural conditions based on Islamic Values. And Teachers themselves must be qualified in their position as professional teachers. They must always develope innovative learning models and have full responsibility with their duties. They also must play their role as a conselor to give intensive guidances to their students specially students who have many dificulties both in academic problems and non academic. Finally, teachers must be commited with their ethic codes so that they become a good model for their students.